Fast and Uniform Optically-Switched Data Centre Networks Enabled by Amplitude Caching - Gerard, Thomas; Clark, Kari; Funnell, Adam; Shi, Kai; Thomsen, Benn; Watts, Philip; Jozwik, Krzysztof; Haller, Istvan; Williams, Hugh; Costa, Paolo; Ballani, Hitesh (Optical Fiber Communication Conference (OFC), 2021)
Data centres are fast approaching a networking bottleneck, where their incumbent electrically-switched networks may struggle to keep pace with the exponentially growing demand for bandwidth. This looming crunch has renewed interest in fast optical circuit switching (OCS), which can be used to create flat, energy-efficient, low latency networks. A wide variety of OCS architectures have been proposed based on wavelength routing, space switching, or a combination thereof, but all OCS systems face the common challenges of varying optical loss and phase across the network paths. These effects can introduce baseline wander and symbol-missampling at the receiver and are particularly hard to account for in sub-microsecond granularity switching systems. However, the data centre represents a unique, closed environment in which the loss and phase changes between sourced-destination pairs are relatively stable; hence, instead of discovering the phase and gain offsets through complex circuits at burst-granularity, they can be remembered or cached and applied at either end. Previously, we have demonstrated that fast clock phase recovery can be achieved by creating a synchronous data centre network that applies clock phase caching (CPC) to phase-align all transceivers with sub-bit precision. In this work, we extend this principle to ‘amplitude caching’, in which optical equalisation is applied prior to transmission (or reception) to mitigate baseline wander in fast burst-mode transceivers. We combine amplitude and phase caching in a generic space-and wavelength switched testbed to create a power- and phase-uniform OCS system, for the first time. By testing our system with real time 25 Gbps on-off keying (OOK) burst data, we demonstrate low-penalty burst switching that permits the creation of highly scalable, flat, energy efficient, OCS data centre networks.